If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(3p + 4) + -14 = 3(4p + 8) Reorder the terms: -7(4 + 3p) + -14 = 3(4p + 8) (4 * -7 + 3p * -7) + -14 = 3(4p + 8) (-28 + -21p) + -14 = 3(4p + 8) Reorder the terms: -28 + -14 + -21p = 3(4p + 8) Combine like terms: -28 + -14 = -42 -42 + -21p = 3(4p + 8) Reorder the terms: -42 + -21p = 3(8 + 4p) -42 + -21p = (8 * 3 + 4p * 3) -42 + -21p = (24 + 12p) Solving -42 + -21p = 24 + 12p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-12p' to each side of the equation. -42 + -21p + -12p = 24 + 12p + -12p Combine like terms: -21p + -12p = -33p -42 + -33p = 24 + 12p + -12p Combine like terms: 12p + -12p = 0 -42 + -33p = 24 + 0 -42 + -33p = 24 Add '42' to each side of the equation. -42 + 42 + -33p = 24 + 42 Combine like terms: -42 + 42 = 0 0 + -33p = 24 + 42 -33p = 24 + 42 Combine like terms: 24 + 42 = 66 -33p = 66 Divide each side by '-33'. p = -2 Simplifying p = -2
| 4x-y-z=7 | | y=1/z=3 | | 2=7-3x | | 67/7 | | 45mi/h= | | Z/3-8-4 | | -5(-4/15) | | -x-8y+2=10 | | 5x-5(-4/15)=4 | | 7/3x-2=12 | | y=1.75x+1 | | -6+-3+-9-(-2)= | | r-1.8=9 | | 50/15 | | 5t^2+t-42=0 | | e^12+e^6=0 | | -8x=9x | | 8x+4=4x-12(x-1) | | 10y^2-41y+40=0 | | 144=b^2-12b | | 8n+56= | | 6/7÷3/28 | | 5xa-18-4a=-36 | | 5*a-18-4a=-36 | | 71=5(3k-8)-2(3k+2) | | 3(-4)6-2(6)(-9)-72+108= | | 3(-4)6-2(6)(-9)(-72)+108= | | 2x+8x-1=14+5x | | 24x+15=6x+17 | | 34(6x+9)=14 | | (y+5)(y-4w-2)=0 | | .11y+.06(y+7000)=1440 |